Phenomenological Thomism: A Prooemium - Engelland, Chad (New blackfriars, 2024)
This paper introduces Phenomenological Thomism by accomplishing the three tasks Thomas Aquinas sets for every prooemium. First, to promote goodwill (beniuolus), it shows how fruitful Phenomenological Thomism promises to be by arguing that it unites the strengths of two complementary alternatives to the modern starting point. Second, to make teachable (docilis), it delineates the principal vectors of phenomenological engagement, including philosophy of nature, philosophical anthropology, ethics, epistemology, metaphysics, philosophical theology, and revealed theology. Third, to arouse attention (attentus), it focuses on the theme of manifestation to highlight the challenge of bringing the two traditions together. In this way, the prooemium encourages the further development of Phenomenological Thomism as a research program involving countless scholars and an infinity of tasks.